(untitled) (Research, Society and Development, 2025)
Odontogenic infections can directly impact the airways. The present study aimed to evaluate the upper airway as a prognostic factor and its influence on treating odontogenic infections via computed tomography. Data were obtained from 28 patients with odontogenic infections who required hospitalization between September 2018 and November 2019. The collected variables included medical history, vital signs, infection history, previous antibiotic therapy, and hospital stay. The laboratory test results were analyzed upon admission and 48 hours after the surgical procedure, and the laboratory risk indicator for necrotizing fasciitis (LRINEC) index was calculated. The airway was assessed via calculations of volume and the shortest retroglossal distance. Spearman’s statistical test was used to study the data. The CRP value at admission was correlated with the airway volume at +0.107 and the AP/LT index at +0.352, with a significance level of 0.066. The LHS showed a correlation coefficient for airway volume of +0.066 and a correlation for the AP/LT index of +0.248, with a significance level of 0.203. The LRINEC index was correlated with the airway volume at -0.027 and with the AP/LT index at +0.332, with a significance level of 0.084. The airway is altered in patients with odontogenic infection; this phenomenon must be better defined, considering that the compression of the airway and the location in which it is most constricted can indicate severity.